Dampak Covid-19 Pada Tren Perkembangan Perdagangan Kriptografi (Crypto-Currency) Studi Kasus Bitcoin Di Indonesia - Mohammad Kurniawan Darma Putra (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2021)
During this pandemic, many changes have occurred, ranging from income, lifestyle, and job opportunities. This is due to the many rules and policies made by the government in order to contain the spread of COVID-19. There are many changes that occur in society, many have changed the direction of community activities such as making savings in spending, conducting online-based food business activities, and trading using stocks or crypto. In this case the author discusses crypto trading, especially bitcoin in Indonesia during the covid-19 pandemic. This study aims to determine the impact of Covid-19 on the development of crypto or bitcoin trading in Indonesia today. In this paper, the researcher uses library research, namely in the process of collecting data, it is not necessary to go directly to the field but take various reference sources that support this research. This research is a type of qualitative research. Data collection techniques are listening and recording important information in conducting data analysis by means of data reduction, data presentation and drawing conclusions so as to get an overview of the conclusions from the literature study that will be developed in this study and for data validation using triangulation of data sources. The results of the author's analysis are that during the Covid-19 pandemic Cryptocurrency as a Form of Investment for the Indonesian Community, especially for Bitcoin trading, experienced a very significant increase, this is also inseparable from news from all media such as Youtube, newspapers, magazines, articles, and advertisements. trading service provider platforms and even a lot of training carried out by traders to be able to socialize bitcoin so that it becomes a trend for young people and business people in Indonesia, the average age of traders in Indonesia is 20-30 years. Based on data, the increase in bitcoin trading in 2018 reached 1 T/day and in 2021 during the COVID-19 pandemic, daily crypto trading transactions as of July 2021 reached IDR 2.3 trillion with the number of crypto customers reaching 7.4 million people. In fact, in 2020 the number was 4 million people and in 2018 there were 1.1 million people which can be concluded that the increase in crypto customers and transactions is greatly increasing. The limitations of this research include the mass area data which is very much interested in bitcoin and how to deal with risks if the value of bitcoin drops and understanding for ordinary people in crypto trading. This research is very useful for all circles, both practitioners and academics because the digital era plays a very important role in the world of education and knowledge.